2009
DOI: 10.1902/jop.2009.080669
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Inhibit the Expression of Collagens Type I and III by Human Gingival Fibroblasts

Abstract: AGEs may suppress the cell viability of HGFs and downregulate the expression of types I and III collagen by the cells. Further investigations are warranted to clarify the molecular mechanisms of AGEs in the regulation of cell function and collagen metabolism in patients with diabetes and periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…This effect is likely due to the ability of AGEs to inhibit cell proliferation, downregulate collagen expression, induce collagen cross-linking and inflammatory responses that, in turn, impair wound healing. 5759 Thus, in Akita −/− mice, hyperglycemia likely leads to accumulation of AGEs in pulp and periodontal structures and compounds the detrimental effects of hyperglycemia on dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is likely due to the ability of AGEs to inhibit cell proliferation, downregulate collagen expression, induce collagen cross-linking and inflammatory responses that, in turn, impair wound healing. 5759 Thus, in Akita −/− mice, hyperglycemia likely leads to accumulation of AGEs in pulp and periodontal structures and compounds the detrimental effects of hyperglycemia on dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this product is the above reported HbAlc. Subsequently, a complex series of molecular reactions resulting in the formation of molecules called "Advanced Glycosylation End products" (AGEs) take place [98,99]. The AGEs are irreversible and belong to a heterogeneous group including carboxymethyllysine (a modified amino acid that accumulates with age in human lens proteins and collagen), the more predominant AGE in diabetic patients and related with tissue aging [100].…”
Section: Diabetes and Periodontitismentioning
confidence: 99%
“…Summarizing, hyperglycemia determines AGE deposition in the collagenous matrix of the periodontal ligament and the alveolar bone matrix, and in BM of gingival capillary walls [99] associated to increased oxidation, altered PMN functions and atheroma formation, interferes with normal periodontal wound healing, perpetuating periodontal disease in the diabetics [84,92].…”
Section: Diabetes and Periodontitismentioning
confidence: 99%
“…Increased AGEs are correlated to inhibited expression of collagen type I and type III in human gingival fibroblasts [21]. Several studies have shown that patients with incisional hernia have a decreased collagen type I/III ratio in the scar of the abdominal wall, the skin and in the uninjured fascia laterally to the scar postoperatively [8, 22–24].…”
Section: Discussionmentioning
confidence: 99%